Evaluation of D-dimer ELISA Test in Elderly Patients with Suspected Pulmonary Embolism - Tardy, Bernard; Tardy-Poncet, Brigitte; Viallon, Alain; Lafond, Pierre; Page, Y.; Venet, Christophe; Bertrand, Jean C. (Thrombosis and Haemostasis, 1998)
Study Objective: To determine the clinical usefulness of D-dimer ELISA test in elderly patients with clinically suspected pulmonary embolism (PE). Design: Prospective cohort study. Patients: Ninety-six consecutive outpatients older than 70 years with a duration of symptoms shorter than one week and without metastatic cancer or recent surgery, trauma, infection, stroke, myocardial infarction, deep vein thrombosis (DVT) or PE, or treatment with curative doses of heparin or oral anticoagulant. Intervention: All patients underwent at least ventilation/perfusion scan and bilateral ultrasonic duplex scan and a blood sample collection within 24 hours of admission. When necessary a pulmonary angiography and/or a bilateral venography were also performed. Patients were classified as follows: (1) PE-positive; positive angiography or high probability V/Q scan and deep vein thrombosis (proven either by venography or by ultrasonic duplex scan) or non high probability V/Q scan and either DVT (proven at presentation by venography or by ultrasonic duplex scan) or symptomatic thromboembolic event within 3 months of follow-up; or (2) PE-negative; normal V/Q scan or normal angiography or non high probability V/Q scan and either negative ultrasonic duplex scan or normal venography and low clinical probability and absence of symptomatic thromboembolism within 3 months of follow-up. D-dimer measurements were performed using both a conventional and a single semi-quantitative ELISA test (Asserachrom D-di, Instant I.A.D-dimer). Results: Using a cutoff value of 500 ng/ml, the conventional ELISA D-dimer test showed a sensitivity and a negative predictive value of 100% with poor specificity and positive predictive value of 14.3% and 45.5% respectively. The new rapid semi-quantitative D-dimer test displays worse results with sensitivity, negative predictive value, specificity and positive predictive value of 92.3%, 82.4%, 25% and 46% respectively. Conclusion: In a geriatric population, conventional ELISA D-dimer is a good marker to exclude PE but, due to the comorbid conditions, only a few patients presented with D-dimer values less than 500 ng/ml.